Pharmacological Validation of a Mechanical Conflict-Avoidance Assay with Osteoarthritic Pain in Rats - Rosenborg, Martin (My University, 2024)
Commonly used pre-clinical pain assays measure evoked responses to noxious stimuli and provide limited insight into the affective-motivational effect of chronic pain. New assays that can quantify an animal’s voluntary behaviour are therefore needed in the development of more effective pain medications for osteoarthritis (OA). One such non-evoked pain assay is the Mechanical Conflict- Avoidance (MCA) assay. The goal of this thesis project is to validate MCA, with the primary hypothesis being that it can show a statistically significant difference in the voluntary behaviour of rats with induced OA-like joint pain compared to rats with a corresponding sham procedure. As a secondary hypothesis, MCA can show the effectiveness of clinically used reference compounds in mitigating pain behaviour. MCA was validated using male Wistar rats with monoarthritic pain induced by an injection of either Complete Freund’s Adjuvant (CFA) in the ankle joint or monosodium iodoacetate (MIA) in the knee joint. Locomotor activity in MCA was measured using various endpoints. Naproxen and pregabalin were used to test the pharmacological effect on behaviour. As positive controls, mechanical hypersensitivity was tested with von Frey filaments and weight bearing was tested using CatWalkTM. The results were analysed with ANOVA or Kruskal-Wallis. MCA showed a significant difference between the activity score of rats with CFA ankle joint pain and a sham group three days post-injection. Although pregabalin did not affect weight bearing in rats with MIA, it mitigated mechanical sensitization in the CFA treated rats and was found to maintain activity levels in the MCA assay with both the CFA ankle and MIA knee pain models. This project confirmed that the MCA assay’s aversive light stimulus and noxious probes are in conflict with the rat’s innate motivation to explore its environment and that an activity score can be used to illustrate the affective component of joint pain. However, the assay’s sensitivity was found to be dependent on the used pain model and the number of times the rats were exposed to the assay. The MCA assay can be used alongside other pain assays to provide insight into the effects of pain medication on voluntary animal behaviour, especially in relation to motivation.
Keywords: nociception, osteoarthritis, mechanical sensitivity, method validation